2018
DOI: 10.1161/circgen.117.002038
|View full text |Cite
|
Sign up to set email alerts
|

Multigenic Disease and Bilineal Inheritance in Dilated Cardiomyopathy Is Illustrated in Nonsegregating LMNA Pedigrees

Abstract: Background: We have previously described 19 pedigrees with apparent lamin (LMNA)-related dilated cardiomyopathy (DCM) manifesting in affected family members across multiple generations. In 6 of 19 families, at least one individual with idiopathic DCM did not carry the family’s LMNA variant. We hypothesized that additional genetic cause may underlie DCM in these families. Methods: Affected family members underwent exome sequencing to identify additional genetic cause of DCM in the 6 families with non-segregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…In the same context, Gifford et al (2018) showed that a human congenital heart defect, the left ventricular non-compaction cardiomyopathy, can be caused by a combination of rare, inherited heterozygous missense variants (Gifford et al 2018). Most recently, Cowan et al (2018) demonstrated that additional genetic variants underlie dilated cardiomyopathy in 6 families with non-segregating LMNA pedigrees and support multigenic and bilineal inheritance in these families (Cowan et al 2018). In the light of all these studies and the thorough genetic analysis of the present family, our results provide further evidence of oligogenic pattern of inheritance in complex cardiac disorder such as sudden cardiac death.…”
Section: Discussionmentioning
confidence: 98%
“…In the same context, Gifford et al (2018) showed that a human congenital heart defect, the left ventricular non-compaction cardiomyopathy, can be caused by a combination of rare, inherited heterozygous missense variants (Gifford et al 2018). Most recently, Cowan et al (2018) demonstrated that additional genetic variants underlie dilated cardiomyopathy in 6 families with non-segregating LMNA pedigrees and support multigenic and bilineal inheritance in these families (Cowan et al 2018). In the light of all these studies and the thorough genetic analysis of the present family, our results provide further evidence of oligogenic pattern of inheritance in complex cardiac disorder such as sudden cardiac death.…”
Section: Discussionmentioning
confidence: 98%
“…Dilated cardiomyopathy is one of the most common causes of heart failure and sudden cardiac death in young people [3]. LMNA is one of the most common causal genes of CCD and DCM [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Dilated cardiomyopathy is one of the most common causes of heart failure and sudden cardiac death in adolescents. 3 Different genetic mutations may result in different onset ages and severity of dilated cardiomyopathy. Lamins A and C, encoded by LMNA gene, are nuclear intermediate filament proteins that form one of the major structural components of the lamina network, which underlies and mechanically supports the nuclear envelope.…”
Section: Discussionmentioning
confidence: 99%